Market and society in Korea : interest, institution and the textile industry - McNamara, Dennis L. (Routledge advances in Korean studies ;, 2002)
"How did industrial structures in textiles evolve in the absence of sophisticated market-supporting institutions? Assessing the roles of capital, labour, and state, Dennis McNamara discovers a distinctive style of interest bargaining to bridge uncertainties and foster entrepreneurship. The textile industry serves as a microcosm of the broader social changes of the past five decades. Dramatic transitions from family firms to professional capitalism, from state direction to regulation, and from company unions to industry federations take centre stage. Moving among executives, labour leaders, and state officials, the author charts development across the crucible of contending interests. Stretching from high technology to labour-intensive production, the textile industry offers a new profile of democratization and market liberalization, and recently of globalization and adjustment in the wake of the Asian financial crisis."--BOOK JACKET.